Aortic root replacement with Medtronic Freestyle bioprosthesis: 25‐year experience. Issue 11 (12th August 2021) - Sweeney, Joseph C.; Smith, Susan A.; Avula, Divya; Trivedi, Jaimin R.; Slaughter, Mark S.; Ganzel, Brian L.
Abstract: Background: Stentless porcine bioprothesis is a surgical strategy to treat aortic root disease. Use has been limited due to the concern for long‐term valve degeneration. This study evaluated the perioperative and late outcomes of patients with aortic root disease requiring root replacement. Methods: A total of 409 patients underwent aortic root replacement by a single surgeon using a stentless porcine bioroot between February 1996 and May 2020. The cohort was divided into two groups (age ≤65 and >65 years). Descriptive statistics were used to analyze the data and Kaplan–Meier curves used to evaluate long‐term outcomes. Results: Patients age >65 years were more likely to be female ( p  = .01), have hypertension ( p  = .01), require circulatory arrest ( p  = .01), and have concomitant coronary artery bypass grafting (CABG) ( p  = .04). Baseline creatinine >1.8 ( p  = .20), diabetes ( p  = .06), and ejection fraction ( p  = .20) were similar between groups. The 1‐, 5‐, and 10‐year survival for patients age ≤65 years were 92%, 87%, and 69%, respectively, significantly better than patients age >65 (88%, 73%, and 43%, respectively) ( p  < .01, Figure 1). The 1‐, 5‐, and 10‐year freedom from reoperation for patients ≤65 years were 99%, 97%, and 93% versus 99%, 98%, and 96% in patients age >65 years, respectively ( p  = .24). Conclusion: Patients with aortic root disease can be treated with acceptable perioperative outcomes, long‐term survival, and low reoperation rates using a stentless porcine bioprothesis. It should be considered irrespective of age due to its excellent durability and freedom from anti‐coagulation requirement.